1927 Haw. Sess. Laws 209-217, AN ACT Regulating the Sale, Transfer and Possession of Certain Firearms and Ammunitions, and Amending Sections 2136, 2137, 2138, 2139, 2140, 2141, 2142, 2143, 2146 and 2147 of the Revised Laws of Hawaii 1925 (the "Small Arms Act"), § 22, § 26 - (:unkn) unknown (General Publisher, 1927)
Required submission of a report upon the sale or disposition of any firearm or ammunition. The report shall be submitted within seven days of the transfer.
--
Keywords: TRANSFER ONLY